ANALYSIS OF RAW MATERIALS FOR THE PRODUCTION OF VEGETABLE MEAT - SHKARAPUTA, ROMAN; МELNYK OKSANA; SPYTSKIY, VIKTOR (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The article is devoted to the analysis of the range of raw materials for the production of plant-based meat, the demand for which is growing rapidly all over the world. Vegetable protein, as a basis for the production of plant-based meat, is in high demand among consumers and producers due to its nutritional and functional properties, as well as its potential to replace animal protein in food products. One of the main components of plant-based meat is protein isolates, which provide the structure and texture of the product, as well as providing the necessary nutrition. The most common options include soy, pea, rice, mung bean, hemp protein, and other plant-based protein sources. These ingredients make it possible to create products with a rich taste and the necessary consistency that will satisfy the needs and tastes of different population groups. Structure formers are used to achieve the required texture and shape of meat. These ingredients can include modified starches, dextrins, cellulose, bread crumbs, cereals, chia and flax seeds, which help bind protein isolates and other components, and provide the necessary density and structure of the meat. Various spices and flavorings (turmeric, cumin, paprika, garlic, onion, fresh herbs) are used to enhance the taste of vegetable meat, and natural dyes such as beetroot juice, turmeric, paprika are added to give the product a suitable color. The use of dyes not only gives the dish an attractive appearance, but also enriches it with useful substances. Each ingredient plays its function, creating the necessary product texture, harmonious taste and high nutritional value. The work evaluates alternative sources of protein from legumes (soybean, pea, mung bean), which can provide high-quality vegetable protein with a specified content of essential amino acids. The justification of the recipe composition and production technology of vegetable meat was carried out. Plant-based meat is an alternative to animal meat for a significant group of the population who have given up the consumption of livestock products and lead a healthy lifestyle. The development and production of such products has a number of advantages for preserving the environment, humane treatment of animals, improving the quality of food and reducing the risk of food-borne diseases, it allows designing the composition of the product with given properties, increasing the nutritional value and expanding the range of products of this series.